Electrical properties of amorphous chalcogenide/silicon heterojunctions modified by ion implantation - Hewak, Dan W. (2014)
Doping of amorphous chalcogenide films of rather dissimilar bonding type and resistivity, namely, Ga-La-S, GeTe, and Ge-Sb-Te by means of ion implantation of bismuth is considered. To characterize defects induced by ionbeam implantation space-charge-limited conduction and capacitance-voltage characteristics of amorphous chalcogenide/silicon heterojunctions are investigated. It is shown that ion implantation introduces substantial defect densities in the films and their interfaces with silicon. This comes along with a gradual decrease in the resistivity and the thermopower coefficient. It is shown that conductivity in GeTe and Ge-Sb-Te films is consistent with the two-type carrier conduction model. It is anticipated that ion implantation renders electrons to become less localized than holes leading to electron conductivity in certain cases as, for example, in GeTe.